Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1785/gssrl.79.5.620
|View full text |Cite
|
Sign up to set email alerts
|

Seismological Report on the 6 August 2007 Crandall Canyon Mine Collapse in Utah

Abstract: A large and tragic underground collapse occurred in the Crandall Canyon coal mine in eastcentral Utah on 6 Aug 2007, causing the loss of six miners and attracting national attention. This collapse was accompanied by a local magnitude (M L) 3.9 seismic event having a location and origin time coincident with the collapse, within current uncertainty limits. Two lines of evidence indicate that most of the seismic wave energy of this event was generated by the mine collapse rather than a naturally-occurring earthqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…One solution is for an event in southwestern Wyoming on 30 January 2000 (number 10, Ⓔ Table S1 in the supplement, M w 4.3, F -test 100%), which is associated with a roof fall (collapse) involving three room and pillar sections in an underground trona mine (McCarter, 2001). The other solution (number 32, Ⓔ Table S1 in the supplement, M w 4.2, F -test 100%) is for the well-documented August 2007 Crandall Canyon coal-mine collapse (see Pechmann et al, 2008). Our solution for the Crandall Canyon event is similar to that of Ford et al (2008).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…One solution is for an event in southwestern Wyoming on 30 January 2000 (number 10, Ⓔ Table S1 in the supplement, M w 4.3, F -test 100%), which is associated with a roof fall (collapse) involving three room and pillar sections in an underground trona mine (McCarter, 2001). The other solution (number 32, Ⓔ Table S1 in the supplement, M w 4.2, F -test 100%) is for the well-documented August 2007 Crandall Canyon coal-mine collapse (see Pechmann et al, 2008). Our solution for the Crandall Canyon event is similar to that of Ford et al (2008).…”
Section: Discussionsupporting
confidence: 76%
“…Before completing the F -test, we suspected that a third event (number 11, Ⓔ Table S1 in the supplement) might also have a significant isotropic component because it occurred within the Willow Creek coal mine, closely in time with seven reported roof falls (Ellenberger et al, 2001;McCarter, 2001). This is one of the largest seismic events associated with underground coal mining in Utah (see Pechmann et al, 2008). The full moment tensor solution has a relatively large isotropic component of 21% (not shown in Ⓔ Table S1 in the supplement as the deviatoric solution is the only one reported).…”
Section: Discussionmentioning
confidence: 99%
“…single or few significant earthquakes (e.g. Ottemöller et al, 2005;Pechmann et al, 2008, Cesca et al, 2011, swarms of weak, shallow earthquakes concentrated in space and time (e.g. Häring et al, 2008;Cuenot et al, 2008), slow slip events (slow earthquakes) with emergent ground motions (e.g.…”
Section: /6mentioning
confidence: 99%
“…MIS that is relocated using the double-difference method can be positioned in absolute space if there is ground truth (Pechmann et al, 2008) or by using the mine layout and sequencing Sonley et al, 2009). For this analysis, the hypoDD locations are shifted relative to the position of the solution from the modified master event locations that was best located using the criteria from the master event technique.…”
Section: Time-varying Velocity Structurementioning
confidence: 99%
“…Recent analyses of both tectonic earthquakes (e.g., Waldhauser and Ellsworth, 2000) and MIS (e.g., Pankow et al, 2008;Pechmann et al, 2008;Rudziński and Dębski, 2012) have demonstrated the ability of enhanced location techniques, such as master event and double-difference methodologies, to improve hypocentral resolution even with velocity model uncertainties and less-than-perfect station distributions. In this study, a variation of the master event methodology and double-difference relocation (Waldhauser and Ellsworth, 2000) with temporal clustering were applied to improve hypocentral resolution of MIS at the TMM.…”
Section: Introductionmentioning
confidence: 99%